ISSUES AND CHALLENGES IN RECONSTRUCTING ISLAMIC ARCHITECTURE IN NUSANTARA: 11 Years of Experience - Utaberta, Nangkula (Universitas Islam Negeri Alauddin Makassar, 2014)
The main objective of this paper is to unfold Issues and challenges in reconstructing Islamic Architecture in Nusantara. Based on the authors experience in discussing and explaining the ideas of Islamic Architecture in Nusantara which in this paper is representing by Indonesia and Malaysia. The discussion will consist of general scenario of Islamic Architecture in the world and Nusantara, problems of physical and non physical documentations of Islamic Architecture artifacts, Issues and problems in defining Islamic Architecture in Nusantara and values and frameworks in reconstructing Islamic Architecture in Nusantara. It is expected that this paper can start and provide a basis and framework for further discussion in redefining Islamic Architecture in this region